Post-millennial Generation’s Prudence on Employability Skills (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Students of post-millennial generation are a hyper intellectual generation with different understudy profiles than previously. They are making pressures for change, and there is a developing rivalry of colleges for worldwide human ability and demand for qualified graduates to do occupations that don't yet exist. Indeed, even the very improvement of technology, which is accessible to many, has roused elite colleges to create inventive projects and novel plans to quicken and improve the teaching and learning process for information and abilities. This research focuses on understanding the level of awareness and readiness of the post-millennial generation student population towards Industry 4.0 employability skillset.  The research design is conclusive in nature and follows a descriptive methodology. The study describes the perception of the post-millennial generation towards their level of awareness and readiness regarding the industrial revolution 4.0. Primary data’s were collected from students of various colleges in Tamil Nadu. Respondents were identified using Random Sampling method. A structured questionnaire was prepared and circulated through online. This qualitative research had received around 300 responses from students of Business Administration and Commerce departments. The skillsets are being ranked from the most important to the least important in terms of awareness of the post-millennial generation as well as their readiness to with stand the tide.